Analisis Pengaruh Ukuran Perusahaan, Umur Perusahaan, Kinerja Perusahaan, Likuiditas Dan Leverage Terhadap Kualitas Akrual (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Handayani, Sri; , Dr. Triyono, SE, M.Si (2016)
This study aims to test the impact of firm size, firm age, firm performance, liquidity, and leverage on accrual quality. Population of this study is manufacturing companies listed in Indonesian Stock Exchange during 2010-2014. This study used purposive sampling method to collect the sample. Based on criteria, there were 31 go public companies that match as the sample. The analysis method used multiple regression. The results of this study showed that firm size, firm age and liquidity have not effect on accrual quality, but the firm performance and leverage have the significant effect on accrual quality.